Ethnomathematical Expolarization of The Portibi Temple Building in North Padang Lawas Regency - Mega Utami Hasibuan; Fibri Rakhmawati (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study explores ethnomathematics in the architecture of the Portibi Temple in North Padang Lawas Regency to reveal the relationship between geometric concepts and the symbolic meaning of Hindu-Buddhist culture. A qualitative approach using observation, interviews, and documentation was used to identify mathematical elements in the temple structure. The results show the presence of a cube-shaped solid on the main body of the temple, symbolizing the stability of human life and the connection between the earth and the sky; a cylinder on the roof representing the continuity of life; beams on the stairs and the base of the temple as symbols of sturdiness; and a rectangular pyramid in the interior, reflecting the relationship between humans and the spiritual world. In addition, the rectangular and trapezoidal solid shapes emphasise the principles of proportionality and balance. These findings demonstrate that the geometric forms in the temple serve not only structural functions but are also rich in philosophical values. The implication is that Portibi Temple can be used as an ethnomathematics-based learning resource that links abstract concepts with the local cultural context, thereby making mathematics learning more concrete, meaningful, and fostering students' appreciation of cultural heritage.